2016
DOI: 10.1038/srep24632
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady stagnation-point flow and heat transfer of a special third grade fluid past a permeable stretching/shrinking sheet

Abstract: In this paper, the unsteady stagnation-point boundary layer flow and heat transfer of a special third grade fluid past a permeable stretching/shrinking sheet has been studied. Similarity transformation is used to transform the system of boundary layer equations which is in the form of partial differential equations into a system of ordinary differential equations. The system of similarity equations is then reduced to a system of first order differential equations and has been solved numerically by using the bv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 35 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Howarth7 and Davey8 extended the two-dimensional and axisymmetric flows to the three dimensional case, which is based on boundary layer approximation in the direction normal to the plane. We mention also here the paper by Naganthran et al 9. on the unsteady stagnation-point flow and heat transfer of a special third grade fluid past a permeable stretching/shrinking sheet.…”
mentioning
confidence: 99%
“…Howarth7 and Davey8 extended the two-dimensional and axisymmetric flows to the three dimensional case, which is based on boundary layer approximation in the direction normal to the plane. We mention also here the paper by Naganthran et al 9. on the unsteady stagnation-point flow and heat transfer of a special third grade fluid past a permeable stretching/shrinking sheet.…”
mentioning
confidence: 99%
“…Through these statements, the leading equations that oversee the time-dependent flow are presented as [4,8,26]:…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…is the ratio of temperature. For the purpose of the similarity result, we presume that κ = κ 0 (1 − ct) 3 /x 2 , with κ 0 > 0 being a constant (see Naganthran et al in [8]…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that multiple solutions exist for a specific range of shrinking parameter. Recently, Naganthran 27 bestowed a numerical review for the unsteady flow of third grade fluid past a stretching/shrinking sheet. The multiple branches of solution have been derived using bvp4c routine in MATLAB.…”
Section: Introductionmentioning
confidence: 99%